Obszary występowania „zielonych” miejsc pracy w polskiej gospodarce - Horoszowska, Joanna (Green employment occurrence areas in the Polish economy, 2008)
The article presents the main areas where green employment will come into being, for example: environment friendly agriculture, environment friendly tourism, renewable energy sources, sustainable transport, environment and nature protection.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 22, s. 58-71